2021
DOI: 10.3390/plants10061039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Re-Annotated Genes Provides Insight into Evolutionary Divergence and Expressions of Aquaporin Family in Pepper

Abstract: Aquaporins (AQPs) are known to have a vital role in water transport in all living organisms including agriculturally important crops, but a comprehensive genomic study of AQPs in pepper has not been implemented. Here, we updated previous gene annotations and generated a total of 259 AQP genes from five plants, including pepper. Phylogenetic and motif analyses revealed that a large proportion of pepper AQP genes belong to the specific subgroup of tonoplast intrinsic protein (TIP) subfamily, TIP4. Chromosomal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that gene family analyses using advanced annotation methods could provide novel insights into the structural and functional characteristics of genes (Bayer et al, 2018;Chae et al, 2021;Lee et al, 2021;Guk et al, 2022). We also performed independent annotation updates and comparative analyses of bZIP genes in Solanaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that gene family analyses using advanced annotation methods could provide novel insights into the structural and functional characteristics of genes (Bayer et al, 2018;Chae et al, 2021;Lee et al, 2021;Guk et al, 2022). We also performed independent annotation updates and comparative analyses of bZIP genes in Solanaceae.…”
Section: Discussionmentioning
confidence: 99%
“…These form membrane channel proteins which are present in all branches of life, but plants have the most diversity in aquaporin homologues. Approximately 47 aquaporins have been identified in tomato and around 73 in sweet pepper ( Reuscher et al 2013 ; Lee et al 2021 ). They possess key roles in the transportation of small neutral solutes, metal ions and gases as well as being a critical regulator in plant–water relations.…”
Section: Discussionmentioning
confidence: 99%
“…Pepper (Capsicum annuum L.) is an agriculturally important vegetable in the Solanaceae family [14,15]. Owing to its unique cold climate advantages, Ningxia has become an important pepper-producing area in Northwest China.…”
Section: Introductionmentioning
confidence: 99%